TRIM31 acts as an intermediate molecule in the process by which Snai2 impairs the proliferation of cervical cancer cells - Cui, Nan; Zhang, Yanru; Zhang, Yuan; Wang, Lei; Wang, Haiyan; Zhang, Xiaorui; Tong, Guoqing; Liu, Xian (Frontiers in Oncology, 2025)
Snai2 is a transcription factor that inhibits the proliferation of cervical cancer cells and tumor growth. The expression of Snai2 inhibited the expression of β-catenin and impaired Wnt/β-catenin signaling pathway activity. The results of the RNA sequence in Snai2-overexpressing cervical cancer cells implied a strong correlation between Snai2 and TRIM31 with ubiquitin ligase activity. However, the mechanism by which Snai2 regulates TRIM31 remains unclear. In cervical cancer cells, TRIM31 is highly expressed in cervical cancer cells and carcinoma tissues and promotes the proliferation of cervical cancer cells. Furthermore, overexpression or interference with TRIM31 could increase or inhibit the expression of downstream proteins of the classical Wnt signaling pathway, such as β-catenin, cyclin D1 and c-Myc. To the best of our knowledge, rescue of TRIM31 in Snai2-overexpressing cervical cancer cells restored the expression of β-catenin, cyclin D1 and c-Myc. Finally, Snai2 was shown to transcriptionally inhibit the expression of TRIM31 by recognizing and binding to its E-box located in the promoter region. Our findings provide new evidence that TRIM31 may promote cell proliferation and that Snai2 may impair Wnt/β-catenin signaling pathway activity through the transcriptional inhibition of TRIM31. These findings provide new ideas for the regulation of tumor growth and targeted therapy by Snai2-TRIM31 and the Wnt/β-catenin pathway axis.